HUBUNGAN AKTIVITAS FISIK DENGAN TEKANAN DARAH PADA PENDERITA DIABETES MELLITUS TIPE II DI PUSKESMAS SENTOSA BARU MEDAN - Lumbantoruan, Putri Bertua; Simatupang, Lenny Lusia (JOURNAL SAINS STUDENT RESEARCH, 2026)
Background: Diabetes Mellitus (DM) is one of the diseases that is a major challenge in the health sector, often termed as a Silent Killer. is a metabolic disorder in the body due to various factors, including chronic hyperglycemia and disorders of carbohydrate, fat, and protein metabolism. Physical activity plays a role in overcoming complications, as well as overcoming blood lipid disorders and preventing increased blood pressure. Objective: This study aims to determine the relationship between physical activity and blood pressure in patients with type II diabetes mellitus at the Sentosa Baru Community Health Center in Medan. Method: This study was conducted quantitatively with a correlation design using the Spearman's test. where the goal is to identify the relationship between physical activity and blood pressure in patients with type 2 diabetes mellitus. Results: the results of the analysis of this study indicate that there is a significant relationship between physical activity and blood pressure in patients with type II diabetes mellitus at the Sentosa Baru Community Health Center with a p-value = 0.000 (<0.05), this indicates that the higher the physical activity, the better the blood pressure. Conclusion: There is a significant relationship between physical activity and blood pressure in patients with type II diabetes mellitus at the Sentosa Baru Community Health Center. Therefore, it is important for patients with type II diabetes to engage in physical activity, at least moderate activity, to maintain stable blood pressure.